Electrolyte, electrochemical device and electronic device containing the same

By using electrolyte containing compounds of formula (I-A) in lithium-ion batteries, a stable solid-state interface film is formed, and the problem of degradation of cycling performance and high-temperature storage performance caused by electrolyte decomposition is solved, and higher battery performance and better Long service life.

CN115443569BActive Publication Date: 2025-02-25NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180026202.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-28
Publication Date
2025-02-25
Estimated Expiration
2041-12-28

AI Technical Summary

Technical Problem

In the process of increasing the energy density of lithium-ion batteries, the decomposition of the electrolyte is accelerated, resulting in a degradation of cycling performance and high-temperature storage performance.

Method used

An electrolyte containing a compound of the specific formula (I-A) is used, which forms a stable interface mask of positive and negative electrodes in an electrochemical device to inhibit the high-temperature decomposition of the electrolyte.

Benefits of technology

By stabilizing the formation of the interface mask, the circulation performance and high-temperature storage performance of the electrochemical device are improved, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003872501210000011
    Figure BDA0003872501210000011
  • Figure BDA0003872501210000012
    Figure BDA0003872501210000012
  • Figure BDA0003872501210000013
    Figure BDA0003872501210000013
Patent Text Reader

Abstract

The present application provides an electrolyte, an electrochemical device and an electronic device comprising the electrolyte, wherein the electrolyte comprises a compound of formula (I-A). The electrolyte comprising the compound of formula (I-A) is applied to the electrochemical device, so that a stable positive electrode solid interface film can be formed on the positive electrode surface of the electrochemical device and a stable negative electrode solid interface film can be formed on the negative electrode surface, thereby effectively improving the cycle performance and high temperature storage performance of the electrochemical device. The electronic device comprising the electrochemical device also has good high temperature storage performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemistry, and in particular to an electrolyte, an electrochemical device and an electronic device containing the electrolyte. Background Art

[0002] As a new type of mobile energy storage device, secondary batteries (such as lithium-ion batteries) have been widely used in the fields of portable small electronic devices such as mobile phones, laptops, and cameras due to their high energy density, high operating voltage, long cycle life, no memory effect, and green environmental protection. They are gradually expanding to large-scale electric transportation and renewable energy storage. With the wide application of lithium-ion batteries in the above fields, people's requirements for the energy density of lithium-ion batteries are getting higher and higher.

[0003] In order to further improve the energy density of lithium-ion batteries, the methods of increasing the charging voltage or increasing the capacity of active materials are usually adopted. However, both methods will accelerate the decomposition of the electrolyte in the lithium-ion battery, thereby reducing the cycle performance and high temperature (≥60°C) storage performance of the lithium-ion battery. Summary of the invention

[0004] The present application provides an electrolyte, an electrochemical device and an electronic device comprising the electrolyte, so as to improve the cycle performance and high-temperature storage performance of the electrochemical device.

[0005] In a first aspect, the present application provides an electrolyte comprising a compound of formula (IA):

[0006]

[0007] Among them, A 1 Selected from the subunit of formula (IB), the subunit of formula (IC) or the subunit of formula (ID):

[0008]

[0009] X and Y are each independently selected from a subunit of formula (IE), a subunit of formula (IF), a subunit of formula (IG) or a subunit of formula (IH):

[0010]

[0011] Represents the binding site with the adjacent atom; R 12 and R 17 are each independently selected from substituted or unsubstituted C 1 To C 10 Alkyl, substituted or unsubstituted C 2 To C 10 Alkenyl, substituted or unsubstituted C 2To C 10 Alkynyl, substituted or unsubstituted C 6 To C 10 Aryl, substituted or unsubstituted C 3 To C 10 alicyclic hydrocarbon group, substituted or unsubstituted C 1 To C 10 aliphatic heterocyclic group, substituted or unsubstituted C 1 To C 10 When the aromatic heterocyclic group is substituted, each substituent is independently selected from a halogen atom; R 11 , R 13 , R 14 , R 15 , R 16 , R 18 and R 19 are each independently selected from a single bond, a substituted or unsubstituted C 1 To C 10 Alkylene, substituted or unsubstituted C 2 To C 10 alkenylene, substituted or unsubstituted C 2 To C 10 Alkyne, substituted or unsubstituted C 6 To C 10 arylene, substituted or unsubstituted C 3 To C 10 alicyclic hydrocarbon group, substituted or unsubstituted C 1 To C 10 aliphatic heterocyclic group, substituted or unsubstituted C 1 To C 10 When the aromatic heterocyclic group is substituted, each substituent is independently selected from a halogen atom; the heteroatoms in the alicyclic group, aromatic heterocyclic group, alicyclic group and aromatic heterocyclic group are independently selected from N, S or O.

[0012] When an electrolyte comprising a compound of formula (IA) is applied to an electrochemical device, a stable positive electrode solid interface film can be formed on the positive electrode surface and a stable negative electrode solid interface film can be formed on the negative electrode surface of the electrochemical device, thereby further improving the stability of the positive electrode surface and the negative electrode surface, inhibiting the continuous decomposition of the electrolyte at high temperature, thereby improving the cycle performance and high temperature storage performance of the electrochemical device.

[0013] Preferably, the compound of formula (IA) comprises at least one of the following compounds (I-1) to (I-38):

[0014]

[0015]

[0016] In one embodiment of the present application, based on the mass of the electrolyte, the mass percentage of the compound of formula (IA) is W I The content of W is 0.01% to 5%, preferably 0.1% to 1%. I The value of can be 0.01%, 0.1%, 0.5%, 1%, 3%, 5% or any value between any two of the above numerical ranges. I Controlling within the above range is more conducive to improving the cycle performance and high-temperature storage performance of the electrochemical device.

[0017] In one embodiment of the present application, the electrolyte further comprises a compound of formula (II-A):

[0018]

[0019] Among them, R 21 and R 22 are each independently selected from substituted or unsubstituted C 1 To C 5 Alkyl, substituted or unsubstituted C 2 To C 5 Alkenyl, substituted or unsubstituted C 2 To C 5 When substituted, each substituent is independently selected from a halogen atom or a methyl group, R 21 and R 22 A closed loop structure can be formed.

[0020] The addition of the compound of formula (II-A) to the electrolyte can further improve the stability of the positive electrode surface and the negative electrode surface, inhibit the continuous decomposition of the electrolyte at high temperature, reduce the consumption required for the electrolyte to undergo redox reaction, and inhibit the gas production of the electrolyte, thereby further improving the cycle performance and high-temperature storage performance of the electrochemical device.

[0021] Preferably, the compound of formula (II-A) comprises at least one of the following compounds (II-1) to (II-12):

[0022]

[0023] In one embodiment of the present application, the electrolyte satisfies at least one of the following (a) or (b): (a) based on the mass of the electrolyte, the mass percentage content W of the compound of formula (II-A) II 0.05% to 3%, preferably 0.1% to 1%; (b) based on the mass of the electrolyte, the mass percentage content of the compound of formula (IA) W I The mass percentage content W of the compound of formula (II-A) IISatisfy: 0<W I / W II ≤10, preferably 0.25≤W I / W II ≤5.

[0024] For example, W II The value of can be 0.05%, 0.1%, 1%, 2%, 3% or any value between any two of the above numerical ranges. II Controlling within the above range is more conducive to improving the cycle performance and high-temperature storage performance of the electrochemical device.

[0025] For example, W I / W II The value of can be 0.1, 0.17, 0.25, 0.5, 5, 10 or any value between any two of the above ranges. I / W II The value of is controlled within the above range, so that the compound of formula (IA) and the compound of formula (II-A) can play a synergistic role, which is more conducive to improving the cycle performance and high temperature storage performance of the electrochemical device.

[0026] In one embodiment of the present application, the electrolyte further includes a first lithium salt, the first lithium salt including lithium difluorophosphate (LiPO 2 F 2 ), lithium difluorobis(oxalate)phosphate (LiDFOP) or lithium tetrafluorooxalatephosphate. The addition of the first lithium salt to the electrolyte can further improve the film-forming effect of the positive electrode solid interface film on the positive electrode surface, reduce the contact between the electrolyte and the positive electrode, and inhibit the gas generation of the electrolyte. Thereby further improving the cycle performance and high temperature storage performance of the electrochemical device.

[0027] In one embodiment of the present application, based on the mass of the electrolyte, the mass percentage of the first lithium salt is W L1 For example, W L1 The value of can be 0.1%, 0.3%, 0.8%, 1% or any value between any two of the above ranges. L1 Controlling within the above range is more conducive to improving the cycle performance and high-temperature storage performance of the electrochemical device.

[0028] In one embodiment of the present application, the electrolyte further comprises a sulfur-oxygen double bond compound, and the sulfur-oxygen double bond compound comprises a compound of formula (III-A):

[0029]

[0030] Among them, A 3Any one selected from the group consisting of a subunit of formula (III-B), a subunit of formula (III-C), a subunit of formula (III-D), a subunit of formula (III-E), a subunit of formula (III-F), a subunit of formula (III-G), a subunit of formula (III-H) or a subunit of formula (III-I):

[0031]

[0032] Represents the binding site with the adjacent atom; R 31 and R 32 are each independently selected from substituted or unsubstituted C 1 To C 5 Alkyl, substituted or unsubstituted C 2 To C 10 Alkenyl, substituted or unsubstituted C 2 To C 10 Alkynyl, substituted or unsubstituted C 3 To C 10 alicyclic group, substituted or unsubstituted C 6 To C 10 Aryl, substituted or unsubstituted C 1 To C 6 aliphatic heterocyclic group, substituted or unsubstituted C 1 To C 6 Aromatic heterocyclic group, substituted or unsubstituted C 1 To C 3 The sulfonyloxyalkyl group, when substituted, each substituent is independently selected from a halogen atom, a C 1 To C 3 Alkyl, C 2 To C 3 Alkenyl or C 2 To C 3 The alkynyl group, R 31 and R 32 A closed ring structure can be formed; the heteroatoms in the alicyclic group and the aromatic heterocyclic group independently include N, S or O.

[0033] The addition of sulfur-oxygen double bond compounds into the electrolyte can enhance the antioxidant capacity of the electrolyte, reduce the possibility of oxidation of the positive electrode active material, and, in the case of lithium deposition at the negative electrode, form a protective film on the surface of metallic lithium to inhibit the decomposition and heat generation of metallic lithium and the electrolyte, thereby enhancing the protection of the negative electrode active material and the positive electrode active material, thereby further improving the cycle performance, high temperature storage performance and floating charge performance of the electrochemical device.

[0034] Preferably, the compound of formula (III-A) comprises at least one of the following compounds (III-1) to (III-53):

[0035]

[0036]

[0037] More preferably, the compound of formula (III-A) comprises at least one of the following compounds:

[0038]

[0039] In one embodiment of the present application, the electrolyte satisfies at least one of the following (c) or (d):

[0040] (c) Based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound W S 0.01% to 10%, preferably 0.1% to 8%;

[0041] (d) The mass percentage of the compound of formula (IA) based on the mass of the electrolyte I Mass percentage of sulfur-oxygen double bond compounds W S Satisfy: 0<W I / W S ≤1, preferably, 0.1≤W I / W S ≤0.3.

[0042] For example, W S The value of can be 0.01%, 0.1%, 4%, 8%, 10% or any value between any two of the above ranges. S Controlling within the above range is more conducive to improving the cycle performance, high temperature storage performance and floating charge performance of the electrochemical device.

[0043] For example, W I / W S The value of can be 0.01, 0.063, 0.1, 0.125, 0.3, 0.5, 1 or any value between any two of the above ranges. I / W S The value of is controlled within the above range, so that the compound of formula (IA) and the sulfur-oxygen double bond compound play a synergistic role, which is more conducive to improving the cycle performance, high temperature storage performance and floating charge performance of the electrochemical device.

[0044] In one embodiment of the present application, the electrolyte further comprises a polynitrile compound, and the polynitrile compound comprises at least one of the following compounds (i-1) to (i-16):

[0045]

[0046] The addition of the polynitrile compound into the electrolyte enables the compound of formula (IA) and the polynitrile compound to exert a synergistic effect, further improving the high-temperature storage performance and floating charge performance of the electrochemical device.

[0047] In one embodiment of the present application, based on the mass of the electrolyte, the mass percentage content of the polynitrile compound is W D The ratio of W to MW is 0.3% to 10%, preferably 2% to 10%. D The value of can be 0.3%, 1%, 2.5%, 3%, 5%, 10% or any value between any two of the above numerical ranges. D Controlling within the above range is more conducive to improving the high-temperature storage performance and floating charge performance of the electrochemical device.

[0048] In one embodiment of the present application, the electrolyte further includes a first non-aqueous organic solvent, and the first non-aqueous organic solvent includes at least one of a cyclic carbonate, a chain carbonate or a carboxylate. The addition of the first non-aqueous organic solvent to the electrolyte can further enhance the stability of the positive electrode solid interface film on the positive electrode surface and the negative electrode solid interface film on the negative electrode surface, and can also improve the flexibility of the positive electrode solid interface film and the negative electrode solid interface film, further increase the protective effect on the positive electrode active material and the negative electrode active material, reduce the contact probability of the positive electrode active material or the negative electrode active material with the electrolyte, so as to suppress the growth of the impedance during the cycle of the electrochemical device, thereby further improving the cycle performance and high temperature storage performance of the electrochemical device.

[0049] In one embodiment of the present application, the cyclic carbonate comprises a compound of formula (IV-A):

[0050]

[0051] Among them, R 4 is selected from substituted or unsubstituted C 1 To C 6 Alkylene, substituted or unsubstituted C 2 To C 6 When substituted, each substituent is independently selected from halogen atoms, C 1 To C 6 Alkyl or C 2 To C 6 Alkenyl.

[0052] Preferably, the compound of formula (IV-A) comprises at least one of the following compounds (IV-1) to (IV-12):

[0053]

[0054] In one embodiment of the present application, the linear carbonate includes at least one of dimethyl carbonate, ethyl methyl carbonate, fluoromethyl methyl carbonate, bis(fluoromethyl) carbonate, difluoromethyl methyl carbonate, ethyl(fluoromethyl) carbonate, difluoromethyl ethyl carbonate, 2-fluoroethyl methyl carbonate, 2-fluoroethyl(fluoromethyl) carbonate, 2,2-difluoroethyl methyl carbonate, 2,2-difluoroethyl ethyl carbonate, 2,2,2-trifluoroethyl ethyl carbonate, (2-fluoroethyl) ethyl carbonate, bis(2-fluoroethyl) carbonate, 2,2-difluoroethyl(2-fluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, bis(2,2,2-trifluoroethyl) carbonate, methyl propyl carbonate or ethyl propyl carbonate; the carboxylic acid ester includes at least one of methyl formate, ethyl formate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate (EP), 2,2-difluoroethyl acetate or 2,2-difluoroethyl ethyl acetate.

[0055] In one embodiment of the present application, the electrolyte satisfies at least one of the following (e) to (g):

[0056] (e) The mass percentage of cyclic carbonate W based on the mass of the electrolyte H 0.01% to 30%, preferably 0.1% to 30%;

[0057] (f) the mass ratio of the cyclic carbonate to the linear carbonate is (10-60):40;

[0058] (g) The mass ratio of cyclic carbonate to carboxylic acid ester is (10-60):(20-60).

[0059] For example, W H The value of can be 0.01%, 5%, 15%, 20%, 25%, 30% or any value between any two of the above ranges. The mass percentage content of cyclic carbonate W H Controlling within the above range is more conducive to improving the cycle performance and high temperature storage performance of the electrochemical device. H The value of is controlled within the above preferred range, which can further improve the cycle performance of the electrochemical device.

[0060] For example, the mass ratio of the cyclic carbonate to the linear carbonate can be 10:40, 15:40, 20:40, 40:40, 55:40, 60:40 or any value between any two of the above numerical ranges. The mass ratio of the cyclic carbonate to the linear carbonate is controlled within the above range, so that the cyclic carbonate and the linear carbonate play a synergistic role, which is more conducive to improving the cycle performance and high temperature storage performance of the electrochemical device.

[0061] For example, the mass ratio of the cyclic carbonate to the carboxylate can be 10:20, 15:25, 55:50, 60:60 or any value between any two of the above ranges. The mass ratio of the cyclic carbonate to the carboxylate is controlled within the above range so that the cyclic carbonate and the carboxylate play a synergistic role, which is more conducive to improving the cycle performance and high temperature storage performance of the electrochemical device.

[0062] In one embodiment of the present application, the electrolyte further comprises a second lithium salt, and the second lithium salt comprises a compound of formula (VA):

[0063]

[0064] Among them, A 51 , A 52 , A 53 and A 54 are each independently selected from a halogen atom, a group of formula (VB), a group of formula (VC) or a group of formula (VD), A 51 , A 52 , A 53 and A 54 Two adjacent groups in can form a closed ring structure:

[0065]

[0066] Represents the binding site with the adjacent atom; O in the two binding sites of the group of formula (VC) is connected to B, k is 0 or 1; R 51 and R 53 are each independently selected from substituted or unsubstituted C 1 To C 6 Alkyl, substituted or unsubstituted C 2 To C 6 When substituted, each substituent is independently selected from a halogen atom; R 52 is selected from substituted or unsubstituted C 1 To C 6 Alkylene, substituted or unsubstituted C 2 To C 6 When the alkenyl group is substituted, each substituent is independently selected from a halogen atom.

[0067] Preferably, the compound of formula (VA) comprises lithium tetrafluoroborate (LiBF 4 ), lithium bis(oxalatoborate) (LiB(C 2 O 4 ) 2 , LiBOB) or lithium difluorooxalatoborate (LiBF 2 (C 2 O 4), LiDFOB).

[0068] The addition of the second lithium salt to the electrolyte can form a positive electrode solid interface film on the surface of the positive electrode, and / or form a negative electrode solid interface film on the surface of the negative electrode, thereby maintaining the stability of the positive electrode / electrolyte and negative electrode / electrolyte interfaces, and further improving the cycle performance, floating charge performance and high temperature storage performance of the electrochemical device.

[0069] In one embodiment of the present application, based on the mass of the electrolyte, the mass percentage content of the second lithium salt is W L2 For example, W L2 The value of can be 0.1%, 0.3%, 0.5%, 1%, 2% or any value between any two of the above ranges. L2 Controlling within the above range is more conducive to improving the cycle performance, floating charge performance and high-temperature storage performance of the electrochemical device.

[0070] The electrolyte of the present application may further include a third lithium salt. The present application has no particular restrictions on the type of the third lithium salt, as long as it can achieve the purpose of the present application. For example, the third lithium salt includes lithium hexafluorophosphate (LiPF 6 ), lithium hexafluoroantimonate (LiSbF 6 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium perfluorobutanesulfonate (LiC 4 F 9 SO 3 ), lithium perchlorate (LiClO 4 ), lithium aluminate (LiAlO 2 ), lithium tetrachloroaluminate (LiAlCl 4 ), Lithium Bissulfonyl Imide (LiN(C x F 2x+1 SO 2 )(C y F 2y+1 SO 2 ), wherein x and y are each independently selected from a natural number from 0 to 6), lithium chloride (LiCl), lithium fluoride (LiF) and at least one thereof.

[0071] The electrolyte of the present application may also include a second non-aqueous organic solvent. The present application does not particularly limit the type of the second non-aqueous organic solvent, as long as the purpose of the present application can be achieved. For example, the second non-aqueous organic solvent may include an ether solvent, a sulfone solvent or other organic solvent. The ether solvent may include at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, dibutyl ether, tetrahydrofuran, 2-methyltetrahydrofuran or bis(2,2,2-trifluoroethyl) ether. The sulfone solvent may include at least one of ethyl vinyl sulfone, methyl isopropyl sulfone, dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, isopropyl sec-butyl sulfone or cyclopentane. Other organic solvents may include at least one of 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, phosphate ester, propyl propionate, ethylene carbonate (also known as ethylene carbonate, abbreviated as EC), propylene carbonate (also known as propylene carbonate, abbreviated as PC) or diethyl carbonate (DEC). Based on the mass of the electrolyte, the mass percentage of the second non-aqueous organic solvent is 5% to 90%. For example, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or any value between any two of the above numerical ranges.

[0072] The second aspect of the present application provides an electrochemical device, which includes the electrolyte described in any of the above solutions. Therefore, the electrochemical device of the present application has good cycle performance and high temperature storage performance.

[0073] In the present application, the electrochemical device may also include a positive electrode, which generally includes a positive electrode current collector and a positive electrode material layer. In the present application, there is no particular restriction on the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to aluminum foil, aluminum alloy foil or composite current collector, etc. In the present application, there is no particular restriction on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 8μm to 12μm. In the present application, the positive electrode material layer may be arranged on one surface in the thickness direction of the positive electrode current collector, or on two surfaces in the thickness direction of the positive electrode current collector. It should be noted that the "surface" here may be the entire area of ​​the positive electrode current collector, or it may be a partial area of ​​the positive electrode current collector. There is no particular restriction in the present application, as long as the purpose of the present application can be achieved.

[0074] In the present application, the positive electrode material layer includes a positive electrode active material. The present application has no particular restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved, for example, it can include at least one of lithium or transition metal element composite oxides, sulfides, selenides or halides. The present application has no particular restrictions on the above transition metal elements, as long as the purpose of the present application can be achieved, for example, it can include at least one of nickel, manganese, cobalt or iron. Specifically, the positive electrode active material may include LiCoO 2 、LiNiO 2 、LiMnO 2 、LiMn 2 O 4 、Li(Ni a1 Co b1 Mn c1 ) 2 (0 <a1<1,0<b1<1,0<c1<1,a1+b1+c1=1)、LiMn 2 O 4 LiNi 1-y1 Co y1 O 2 (0 <y1<1)、LiCo l-y2 Mn y2 O 2 (0 <y2<1)、LiNi l-y3 Mn y3 O 2 (0 <y3<1)、Li(Ni a2 Mn b2 Co c2 ) 4 (0 <a2<2,0<b2<2,0<c2<2,a2+b2+c2=2)、LiMn 2-z1 Ni z1 O 4 (0 <z1<2)、LiMn 2- z2 Co z2 O 4 (0 <z2<2)、Li(Ni a3 Co b3 Al c3 ) 2 (0 <a3<1,0<b3<1,0<c3<1,a3+b3+c3=1)、LiCoPO 4 or LiFePO 4 At least one of .

[0075] Optionally, the positive electrode active material has a coating layer located on the surface. The present application has no particular restrictions on the compound of the coating layer, as long as the purpose of the present application can be achieved. For example, the compound of the coating layer may be amorphous or crystalline, and the compound of the coating layer may include but is not limited to at least one of an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, or a basic carbonate of a coating element. The above-mentioned coating element may include but is not limited to at least one of Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, or Zr. The present application has no particular restrictions on the preparation method of the coating layer, and a preparation method known in the art can be used, as long as the purpose of the present application can be achieved, such as a spraying method or an impregnation method.

[0076] The positive electrode material layer may also include a positive electrode binder. The present application has no particular limitation on the positive electrode binder as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon.

[0077] In the present application, the positive electrode material layer may also include a conductive agent, and the present application has no particular restrictions on the conductive agent, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to natural graphite, artificial graphite, conductive carbon black (SuperP), carbon nanotubes (CNTs), carbon fibers, flake graphite, Ketjen black, graphene, metal materials or at least one of conductive polymers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.

[0078] Optionally, the positive electrode may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The present application has no particular limitation on the composition of the conductive layer, which may be a conductive layer commonly used in the art, for example, including but not limited to the above conductive agent and the above positive electrode binder.

[0079] In the present application, the electrochemical device may further include a negative electrode, which generally includes a negative electrode current collector. There is no particular limitation on the negative electrode current collector in the present application, as long as the object of the present application can be achieved. For example, it may include, but is not limited to, copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or composite current collector, etc. In the present application, there is no particular limitation on the thickness of the current collector of the negative electrode, as long as the object of the present application can be achieved. For example, the thickness is 4 μm to 12 μm. In the present application, the negative electrode material layer may be disposed on one surface in the thickness direction of the negative electrode current collector, or may be disposed on both surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here may be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. There is no particular limitation in the present application, as long as the object of the present application can be achieved.

[0080] In the present application, the negative electrode material layer includes a negative electrode active material. Among them, there is no particular limitation on the negative electrode active material, as long as the object of the present application can be achieved. For example, it may include, but is not limited to, at least one of a material that can reversibly intercalate / deintercalate lithium ions, lithium metal, lithium metal alloy, a material that can dope / de-dope lithium, or a transition metal oxide.

[0081] The material that can reversibly intercalate / deintercalate lithium ions may include, but is not limited to, carbon materials, and the carbon materials include crystalline carbon and / or amorphous carbon. The crystalline carbon may include, but is not limited to, natural graphite, artificial graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesophase carbon microbead, mesophase pitch, or high-temperature calcined carbon (such as petroleum or coke derived from coal tar pitch) in an amorphous or plate-shaped, flake-shaped, spherical, or fibrous form. The amorphous carbon may include, but is not limited to, at least one of soft carbon, hard carbon, mesophase pitch carbonization product, or calcined coke. The lithium metal alloy includes lithium and at least one metal among Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, or Sn. The material that can dope / de-dope lithium may include, but is not limited to, Si, SiO x (0 < x ≤ 2), Si / C composite, Si-Q alloy (where Q includes at least one of alkali metals, alkaline earth metals, Group 13 to Group 16 elements, transition elements, or rare earth elements, but is not Si), Sn, SnO 2, Sn-C complex, Sn-R (wherein R includes at least one of alkali metal, alkaline earth metal, elements of Groups 13 to 16, transition elements or rare earth elements, but not Sn), etc. Q and R each independently include at least one of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te or Po. The transition metal oxide may include, but is not limited to, vanadium oxide and / or lithium vanadium oxide.

[0082] In the present application, the negative electrode material layer may further include a conductive agent. The present application has no particular limitation on the conductive agent, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of the above conductive agents.

[0083] In the present application, the negative electrode material layer may also include a negative electrode binder. The present application has no particular limitation on the negative electrode binder as long as the purpose of the present application can be achieved. For example, it may include but is not limited to difluoroethylene-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or at least one of nylon.

[0084] Optionally, the negative electrode may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular limitation on the composition of the conductive layer, which may be a commonly used conductive layer in the art, and may include but is not limited to the above conductive agent and the above negative electrode binder.

[0085] The electrochemical device of the present application also includes a diaphragm to separate the positive electrode and the negative electrode, prevent the internal short circuit of the lithium ion battery, allow the electrolyte ions to pass freely, and complete the electrochemical charge and discharge process. The diaphragm in the present application is not particularly limited, as long as the purpose of the present application can be achieved. For example, polyethylene (PE), polypropylene (PP)-based polyolefin (PO)-type diaphragms, polyester films (such as polyethylene terephthalate (PET) films), cellulose films, polyimide films (PI), polyamide films (PA), spandex, aramid films, woven films, non-woven films (non-woven fabrics), microporous films, composite films, diaphragm paper, rolled films or spinning films, etc. At least one. For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide, etc. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the inorganic particles are not particularly limited, for example, they can be selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The binder is not particularly limited, for example, it can be selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The polymer layer contains polymers, and the polymer material includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).

[0086] The electrochemical device of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In some embodiments, the electrochemical device may include, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, or a lithium ion polymer secondary battery.

[0087] The preparation process of the electrochemical device is well known to those skilled in the art, and the present application has no particular limitation. For example, it may include but is not limited to the following steps: stacking the positive electrode, the separator and the negative electrode in order, and winding, folding and other operations as needed to obtain an electrode assembly of a wound structure, placing the electrode assembly in a packaging shell, injecting an electrolyte into the packaging shell and sealing it to obtain an electrochemical device; or stacking the positive electrode, the separator and the negative electrode in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging shell, injecting an electrolyte into the packaging shell and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging shell as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.

[0088] The third aspect of the present application provides an electronic device, which includes the electrochemical device described in the second aspect of the present application. The electronic device has good cycle performance and high-temperature storage performance.

[0089] The electronic devices of the present application are not particularly limited, and may include but are not limited to the following types: laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.

[0090] The present application provides an electrolyte, an electrochemical device and an electronic device comprising the electrolyte, wherein the electrolyte comprises a compound of formula (IA). The electrolyte comprising the compound of formula (IA) is applied to the electrochemical device, so that a stable positive electrode solid interface film can be formed on the positive electrode surface of the electrochemical device and a stable negative electrode solid interface film can be formed on the negative electrode surface, thereby effectively improving the cycle performance and high temperature storage performance of the electrochemical device. The electronic device comprising the electrochemical device also has good high temperature storage performance and cycle performance. DETAILED DESCRIPTION

[0091] In order to make the purpose, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail with reference to the embodiments below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other technical solutions obtained by ordinary technicians in the field belong to the scope of protection of the present application.

[0092] Example

[0093] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods.

[0094] Example 1-1

[0095] <Preparation of positive electrode>

[0096] The positive electrode active material NCM811 (LiNi 0.8 Mn 0.1 Co 0.1 O 2 ), conductive agent acetylene black, and binder polyvinylidene fluoride are mixed in a mass ratio of 96:2:2, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 70wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and the aluminum foil is dried at 120°C for 1h to obtain a positive electrode coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode coated with a positive electrode material layer on both sides. Then, after cold pressing, cutting, and slitting, it is dried under vacuum conditions at 120°C for 1h to obtain a positive electrode with a specification of 74mm×867mm, and a positive electrode compaction density of 3.50g / cm 3 .

[0097] <Preparation of negative electrode>

[0098] The negative electrode active material graphite, the binder styrene butadiene rubber, and the thickener sodium carboxymethyl cellulose (CMC) are mixed in a mass ratio of 97.4:1.4:1.2, and deionized water is added to obtain a negative electrode slurry under the action of a vacuum mixer, wherein the solid content of the negative electrode slurry is 75wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12μm, and the copper foil is dried at 120°C to obtain a negative electrode with a coating thickness of 130μm and a single-sided negative electrode coated with a negative electrode material layer. Repeat the above steps on the other surface of the aluminum foil to obtain a negative electrode with a double-sided negative electrode material layer. Then, after cold pressing, cutting, and slitting, it is dried under vacuum conditions at 120°C for 1h to obtain a negative electrode with a specification of 76mm×851mm, and the compaction density of the negative electrode is 1.80g / cm 3 .

[0099] <Preparation of Electrolyte>

[0100] In an argon atmosphere glove box with a water content of <10 ppm, EC, PC, and DEC were mixed in a mass ratio of 30:30:40 to obtain an organic solvent, and then a third lithium salt, lithium hexafluorophosphate (LiPF 6) and a compound (I-1) of formula (IA) to obtain an electrolyte. 6 The concentration is 1 mol / L. Based on the mass of the electrolyte, the mass percentage of the compound of formula (IA) is W I The content of lithium ion is 0.1%, and the rest is the third lithium salt and the organic solvent.

[0101] <Preparation of Separator>

[0102] Alumina and polyvinylidene fluoride were mixed in a mass ratio of 90:10 and dissolved in deionized water to form a ceramic slurry with a solid content of 50wt%. The ceramic slurry was then evenly coated on one side of a porous substrate (polyethylene, 5μm thick, 39% porosity) using a micro-concave coating method, and dried to obtain a double-layer structure of a ceramic coating and a porous substrate, with a thickness of 3μm.

[0103] Polyvinylidene fluoride (PVDF) and polyacrylate were mixed in a mass ratio of 96:4 and dissolved in deionized water to form a polymer slurry with a solid content of 50wt%. The polymer slurry was then evenly coated on both surfaces of the double-layer structure of the ceramic coating and the porous substrate by a micro-concave coating method, and dried to obtain a diaphragm, wherein the thickness of the single-layer coating formed by the polymer slurry was 2mg / (50×100mm 2 ).

[0104] <Preparation of lithium-ion batteries>

[0105] The positive electrode, separator and negative electrode prepared above are stacked in order, with the separator placed between the positive electrode and the negative electrode to play a role of isolation, and the electrode assembly is wound. The electrode assembly is placed in an aluminum-plastic film packaging bag, and after drying, the electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, degassing, trimming and other processes. The upper limit voltage of the formation is 4.15V, the formation temperature is 70°C, and the formation standing time is 2h.

[0106] Example 1-2 to Example 1-14

[0107] In addition to adjusting the type and mass percentage of the compound of formula (IA) according to Table 1 I , except that the content of the organic solvent changes accordingly, the rest is the same as Example 1-1.

[0108] Example 2-1 to Example 2-7

[0109] Except that the compound of formula (II-A) is further added in accordance with the type and mass percentage shown in Table 2 and the content of the organic solvent is changed accordingly in <Preparation of Electrolyte>, the rest is the same as Example 1-1.

[0110] Example 3-1 to Example 3-4

[0111] Except that the first lithium salt and the content of the organic solvent are further added according to the types and mass percentages shown in Table 3 in <Preparation of Electrolyte>, the rest is the same as Example 1-1.

[0112] Example 4-1 to Example 4-8

[0113] Except that a sulfur-oxygen double bond compound is further added in accordance with the type and mass percentage shown in Table 4 and the content of the organic solvent is changed accordingly in <Preparation of Electrolyte>, the rest is the same as Example 1-1.

[0114] Example 5-1 to Example 5-2

[0115] Except that in <Preparation of Electrolyte>, the compound of formula (II-A), the first lithium salt and the sulfur-oxygen double bond compound, and the content of the organic solvent are optionally added according to the types and mass percentages shown in Table 5, and the contents thereof vary accordingly, the rest are the same as Example 1-1.

[0116] Example 6-1

[0117] <Preparation of positive electrode>

[0118] The positive electrode active material LCO (molecular formula LiCoO 2 ), conductive carbon black, conductive slurry, and binder polyvinylidene fluoride are fully stirred and mixed in an appropriate amount of NMP solvent in a weight ratio of 97.9:0.4:0.5:1.2, and stirred under the action of a vacuum mixer until the system becomes uniform and transparent to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 70wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and the aluminum foil is dried at 120°C for 1h to obtain a positive electrode coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode coated with a positive electrode material layer on both sides. Then, after cold pressing, cutting, and slitting, it is dried under vacuum conditions at 120°C for 1h to obtain a positive electrode with a specification of 74mm×867mm, and the positive electrode compaction density is 4.15g / cm 3 .

[0119] <Preparation of Electrolyte>

[0120] In an argon atmosphere glove box with a water content of <10 ppm, EC, PC, DEC, EP, and propyl propionate were mixed in a mass ratio of 20:20:20:20:20 to obtain an organic solvent, and then a third lithium salt, lithium hexafluorophosphate (LiPF 6 ) and a compound (I-1) of formula (IA) to obtain an electrolyte. 6The concentration is 1 mol / L. Based on the mass of the electrolyte, the mass percentage of the compound of formula (IA) is W I The content of lithium ion is 0.1%, and the rest is the third lithium salt and the organic solvent.

[0121] <Preparation of negative electrode>, <Preparation of separator>, and <Preparation of lithium ion battery> are the same as those in Example 1-1.

[0122] Example 6-2 to Example 6-8

[0123] Except that in <Preparation of Electrolyte>, a polynitrile compound is further added according to the type and mass percentage shown in Table 6, and the content of the organic solvent is changed accordingly, the rest is the same as Example 6-1.

[0124] Example 7-1 to Example 7-7

[0125] Except that cyclic carbonate and chain carbonate were further added in the types and mass percentages shown in Table 7 in <Preparation of Electrolyte>, and the content of organic solvent was changed accordingly, the rest was the same as Example 6-1.

[0126] Example 8-1 to Example 8-6

[0127] Except that the second lithium salt and the content of the organic solvent are further added in accordance with the type and mass percentage shown in Table 8 in <Preparation of Electrolyte>, the rest is the same as Example 6-1.

[0128] Example 9-1 to Example 9-4

[0129] Except that in <Preparation of Electrolyte>, a polynitrile compound, a second lithium salt and a sulfur-oxygen double bond compound are optionally added according to the types and mass percentages shown in Table 9, and the content of the organic solvent varies accordingly, the rest is the same as Example 6-1.

[0130] Comparative Example 1 to Comparative Example 2

[0131] In addition to adjusting the type and mass percentage of the compound of formula (IA) according to Table 1 I , except that the content of the organic solvent changes accordingly, the rest is the same as Example 1-1.

[0132] The lithium ion batteries prepared in the above embodiments and comparative examples were subjected to performance tests using the following testing methods and equipment:

[0133] Cycle capacity retention test:

[0134] At 25°C, the lithium-ion battery is charged to 4.25V at 1C, and then charged to 0.05C at a constant voltage at 4.25V. Then, it is discharged to 2.8V at a current of 4C, and the capacity of the tested lithium-ion battery is recorded as the first cycle capacity. The above charge and discharge process is regarded as one cycle, and the cycle test is performed for 800 cycles. The capacity of the tested lithium-ion battery is recorded as the capacity after the cycle. Cycle capacity retention rate (%) = first cycle capacity / capacity after the cycle × 100%.

[0135] High temperature storage performance test:

[0136] The lithium ion batteries prepared in the examples and comparative examples in Tables 1 to 5 were charged at 25°C at a constant current of 0.5C to 4.25V, and then charged at a constant voltage to a current of 0.05C. The thickness of the lithium ion batteries was tested and recorded as d 01 ; After being placed in an oven at 85°C for 6 hours, the thickness of the lithium-ion battery is measured and recorded as d 1 Thickness expansion ratio of lithium-ion battery after storage at 85℃ for 6h (%) = (d 1 -d 01 ) / d 01 ×100%.

[0137] The lithium ion batteries prepared in the examples in Tables 6 to 9 were charged at 25°C at a constant current of 0.5C to 4.45V, and then charged at a constant voltage to a current of 0.05C. The thickness of the lithium ion batteries was tested and recorded as d 02 , placed in an oven at 85℃ for 24h, and then the thickness of the lithium-ion battery was measured, recorded as d 2 Thickness expansion rate of lithium-ion battery after storage at 85℃ for 24h (%) = (d 2 -d 02 ) / d 02 × 100%. If the thickness expansion rate is greater than 50%, the test is stopped. In Tables 6 to 9, the thickness expansion rate "greater than 50%" means that the thickness expansion rate exceeds 50% when the test time is less than 24h, and the test is stopped.

[0138] Floating charge performance test:

[0139] The lithium-ion battery was discharged at 0.5C to 3.0V at 25°C, then charged at 0.5C to 4.45V, and then charged at a constant voltage of 4.45V to 0.05C. The thickness of the lithium-ion battery was measured and recorded as d 03 , placed in a 45℃ oven, charged at 4.45V constant voltage for 30 days, monitor the thickness change, and record the thickness as d 3 , Li-ion battery float charge thickness expansion rate (%) = (d 3 -d 03 ) / d 03 ×100%, if the thickness expansion rate is greater than 50%, the test is stopped.

[0140] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 to 9:

[0141] Table 1

[0142]

[0143] Note: "\" in Table 1 indicates that there is no corresponding preparation parameter or performance parameter. "-" in Table 1 indicates that the number of cycles of the lithium-ion batteries of Comparative Example 1 and Comparative Example 2 in the cycle capacity retention rate test did not reach 800 cycles.

[0144] It can be seen from Examples 1-1 to 1-9 and Comparative Example 1 that the cycle performance and high temperature storage performance of the lithium ion battery vary with the type of the compound of formula (IA). The lithium ion battery containing the compound of formula (IA) within the scope of the present application has better cycle performance and high temperature storage performance.

[0145] The mass percentage content of the compound of formula (IA) is W I It will also usually affect the cycle performance and high temperature storage performance of lithium-ion batteries. From Example 1-1, Example 1-10 to Example 1-14 and Comparative Example 2, it can be seen that the mass percentage content of the compound of formula (IA) is W I The lithium-ion battery within the scope of this application has better cycle performance and high-temperature storage performance.

[0146] Table 2

[0147]

[0148]

[0149] Note: “\” in Table 2 means there is no corresponding preparation parameter or performance parameter.

[0150] Type and mass percentage of compound of formula (II-A) II , and W I / W II The value of will usually also affect the cycle performance and high temperature storage performance of lithium ion batteries. From Examples 1-1, 2-1 to 2-7, it can be seen that the type and mass percentage content W of the compound of formula (II-A) II , and W I / W II The lithium-ion battery with a value within the range of the present application has good cycle performance and high-temperature storage performance.

[0151] Table 3

[0152]

[0153] Note: “\” in Table 3 means there is no corresponding preparation parameter or performance parameter.

[0154] Type and mass percentage of the first lithium salt W L1 It will also usually affect the cycle performance and high temperature storage performance of lithium-ion batteries. From Example 1-1, Example 3-1 to Example 3-4, it can be seen that the type and mass percentage of the first lithium salt W L1 The lithium-ion battery within the scope of this application has good cycle performance and high-temperature storage performance.

[0155] Table 4

[0156]

[0157] Note: “\” in Table 4 means there is no corresponding preparation parameter or performance parameter.

[0158] Types and mass percentages of sulfur-oxygen double bond compounds W S , and W I / W S The value of will usually also affect the cycle performance and high temperature storage performance of lithium-ion batteries. From Examples 1-1, 4-1 to 4-8, it can be seen that the type and mass percentage of sulfur-oxygen double bond compounds W S , and W I / W S The lithium-ion battery with a value within the range of the present application has good cycle performance and high-temperature storage performance.

[0159] Table 5

[0160]

[0161] Note: “\” in Table 5 means there is no corresponding preparation parameter.

[0162] The compound of formula (IA) can be optionally used in combination with at least two of the compound of formula (II-A), the first lithium salt or the sulfur-oxygen double bond compound to affect the cycle performance and floating charge performance of the lithium ion battery. It can be seen from Examples 1-1, 5-1 and 5-2 that the compound of formula (IA) has good compatibility and superposition with the compound of formula (II-A), the first lithium salt or the sulfur-oxygen double bond compound, and the lithium ion batteries obtained by using the combination have good cycle performance and floating charge performance.

[0163] Table 6

[0164]

[0165] Note: “\” in Table 6 means there is no corresponding preparation parameter or performance parameter.

[0166] Types and mass percentages of polynitrile compounds W D It will also usually affect the high temperature storage performance and floating charge performance of lithium-ion batteries. From Examples 6-1 to 6-8, it can be seen that the type and mass percentage of the polynitrile compound W D The lithium-ion battery within the scope of this application has good high-temperature storage performance and floating charge performance.

[0167] Table 7

[0168]

[0169] Note: “\” in Table 7 means there is no corresponding preparation parameter or performance parameter.

[0170] Type and mass percentage of the first non-aqueous organic solvent W H The mass ratio of the cyclic carbonate to the linear carbonate and the mass ratio of the cyclic carbonate to the carboxylic acid ester usually also have an impact on the cycle performance and high temperature storage performance of the lithium ion battery. It can be seen from Examples 6-1, 7-1 to 7-7 that the type and mass percentage of the first non-aqueous organic solvent W H The lithium ion battery with the mass ratio of cyclic carbonate to linear carbonate and the mass ratio of cyclic carbonate to carboxylic acid ester within the scope of the present application has good cycle performance and high temperature storage performance. It can be seen from Examples 7-1 to 7-5 that the mass percentage content of the first non-aqueous organic solvent is W H The lithium-ion battery within the preferred range of the present application has better cycle performance.

[0171] Table 8

[0172]

[0173]

[0174] Note: “\” in Table 8 means there is no corresponding preparation parameter or performance parameter.

[0175] Type and mass percentage of the second lithium salt W L2 It will also usually affect the cycle performance, floating charge performance and high temperature storage performance of the lithium-ion battery. From Example 6-1, Example 8-1 to Example 8-6, it can be seen that the type and mass percentage of the second lithium salt W L2 The lithium-ion batteries within the scope of the present application have good cycle performance, floating charge performance and high temperature storage performance. Compared with Example 6-1, Examples 8-1 to 8-6 have particularly better cycle performance.

[0176] Table 9

[0177]

[0178] Note: “\” in Table 9 means there is no corresponding preparation parameter or performance parameter.

[0179] The compound of formula (IA) can be optionally used in combination with at least two of the sulfur-oxygen double bond compound, the polynitrile compound or the second lithium salt, which affects the cycle performance, floating charge performance and high temperature storage performance of the lithium ion battery. It can be seen from Example 6-1, Example 9-1 to Example 9-4 that the compound of formula (IA) has good compatibility and superposition with the sulfur-oxygen double bond compound, the polynitrile compound or the second lithium salt, and the lithium ion battery obtained by using the combination has good high temperature storage performance and floating charge performance.

[0180] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. An electrolyte comprising a compound of formula (IA): in, A 1 Selected from the subunit of formula (IB) or the subunit of formula (ID): X and Y are each independently selected from a subunit of formula (IE), a subunit of formula (IF), a subunit of formula (IG) or a subunit of formula (IH): represents the binding site with the neighboring atoms; R 12 is selected from substituted or unsubstituted C1 to C 10 alkyl, substituted or unsubstituted C2 to C 10 alkenyl, substituted or unsubstituted C2 to C 10 substituted or unsubstituted C6 to C 10 aryl, substituted or unsubstituted C3 to C 10 alicyclic hydrocarbon group, substituted or unsubstituted C1 to C 10 alicyclic group, substituted or unsubstituted C1 to C 10 When the aromatic heterocyclic group is substituted, each substituent is independently selected from a halogen atom; R 11 , R 13 and R 14 are each independently selected from a single bond, a substituted or unsubstituted C1 to C 10 alkylene, substituted or unsubstituted C2 to C 10 alkenylene, substituted or unsubstituted C2 to C 10 substituted or unsubstituted C6 to C 10 arylene, substituted or unsubstituted C3 to C 10 alicyclic hydrocarbon group, substituted or unsubstituted C1 to C 10 aliphatic heterocyclic group, substituted or unsubstituted C1 to C 10 When the aromatic heterocyclic group is substituted, each substituent is independently selected from a halogen atom; R 18 and R 19 are each independently selected from substituted or unsubstituted C1 to C 10 alkylene, substituted or unsubstituted C2 to C 10 alkenylene, substituted or unsubstituted C2 to C 10 substituted or unsubstituted C6 to C 10 arylene, substituted or unsubstituted C3 to C 10 alicyclic hydrocarbon group, substituted or unsubstituted C1 to C 10 aliphatic heterocyclic group, substituted or unsubstituted C1 to C 10 When the aromatic heterocyclic group is substituted, each substituent is independently selected from a halogen atom; The heteroatoms in the alicyclic group, the aromatic heterocyclic group, the alicyclic group and the aromatic heterocyclic group each independently include N, S or O; Based on the mass of the electrolyte, the mass percentage of the compound of formula (IA) is W I 0.01% to 5%.

2. The electrolyte according to claim 1, wherein The compound of formula (IA) includes at least one of the following compounds:

3. The electrolyte according to claim 1, wherein The electrolyte also includes a compound of formula (II-A): Among them, R 21 and R 22 Each is independently selected from a substituted or unsubstituted C1 to C5 alkyl, a substituted or unsubstituted C2 to C5 alkenyl, a substituted or unsubstituted C2 to C5 alkynyl, and when substituted, each substituent is independently selected from a halogen atom or a methyl group.

4. The electrolyte according to claim 3, wherein R 21 and R 22 Form a closed loop structure.

5. The electrolyte according to claim 3 or 4, wherein The compound of formula (II-A) includes at least one of the following compounds (II-1) to (II-12):

6. The electrolyte according to claim 3 or 4, wherein The electrolyte satisfies at least one of the following (a) or (b): (a) Based on the mass of the electrolyte, the mass percentage W of the compound of formula (II-A) II 0.05% to 3%; (b) based on the mass of the electrolyte, the mass percentage W of the compound of formula (IA) I The mass percentage W of the compound of formula (II-A) II Satisfy: 0<W I / W II ≤10.

7. The electrolyte according to claim 1, wherein The electrolyte further includes a first lithium salt, wherein the first lithium salt includes at least one of lithium difluorophosphate, lithium difluorobisoxalate phosphate, or lithium tetrafluorooxalate phosphate.

8. The electrolyte according to claim 7, wherein Based on the mass of the electrolyte, the mass percentage of the first lithium salt is W L1 It is between 0.1% and 1%.

9. The electrolyte according to claim 1, wherein The electrolyte further comprises a sulfur-oxygen double bond compound, wherein the sulfur-oxygen double bond compound comprises a compound of formula (III-A): in, A 3 Any one selected from the group consisting of a subunit of formula (III-B), a subunit of formula (III-C), a subunit of formula (III-D), a subunit of formula (III-E), a subunit of formula (III-F), a subunit of formula (III-G), a subunit of formula (III-H) or a subunit of formula (III-I): represents the binding site with the neighboring atoms; R 31 and R 32 are each independently selected from substituted or unsubstituted C1 to C5 alkyl, substituted or unsubstituted C2 to C 10 alkenyl, substituted or unsubstituted C2 to C 10 substituted or unsubstituted C3 to C 10 alicyclic group, substituted or unsubstituted C6 to C 10 substituted or unsubstituted C1 to C6 alicyclic group, substituted or unsubstituted C1 to C6 aromatic heterocyclic group, substituted or unsubstituted C1 to C3 sulfonyloxyalkyl group, when substituted, each substituent is independently selected from halogen atom, C1 to C3 alkyl group, C2 to C3 alkenyl group or C2 to C3 alkynyl group; The heteroatoms in the alicyclic group and the aromatic heterocyclic group each independently include N, S or O.

10. The electrolyte according to claim 9, wherein R 31 and R 32 Form a closed loop structure.

11. The electrolyte according to claim 9 or 10, wherein The compound of formula (III-A) includes at least one of the following compounds (III-1) to (III-53):

12. The electrolyte according to claim 9 or 10, wherein The compound of formula (III-A) includes at least one of the following compounds:

13. The electrolyte according to claim 9 or 10, wherein The electrolyte satisfies at least one of the following (c) or (d): (c) Based on the mass of the electrolyte, the mass percentage W of the sulfur-oxygen double bond compound S 0.01% to 10%; (d) based on the mass of the electrolyte, the mass percentage of the compound of formula (IA) W I The mass percentage content W of the sulfur-oxygen double bond compound S Satisfy: 0<W I / W S ≤1.

14. The electrolyte according to claim 1, wherein The electrolyte further comprises a polynitrile compound, wherein the polynitrile compound comprises at least one of the following compounds (i-1) to (i-16):

15. The electrolyte according to claim 14, wherein Based on the mass of the electrolyte, the mass percentage of the polynitrile compound is W D It is 0.3% to 10%.

16. The electrolyte according to claim 1, wherein The electrolyte solution further includes a first non-aqueous organic solvent, and the first non-aqueous organic solvent includes at least one of cyclic carbonate, chain carbonate or carboxylate.

17. The electrolyte according to claim 16, wherein The cyclic carbonate includes a compound of formula (IV-A): Among them, R 4 is selected from substituted or unsubstituted C1 to C6 alkylene, substituted or unsubstituted C2 to C6 alkenylene, and when substituted, each substituent is independently selected from a halogen atom, a C1 to C6 alkyl or a C2 to C6 alkenyl.

18. The electrolyte according to claim 17, wherein The compound of formula (IV-A) includes at least one of the following compounds (IV-1) to (IV-12):

19. The electrolyte according to claim 16, wherein The linear carbonate comprises at least one of dimethyl carbonate, ethyl methyl carbonate, fluoromethyl methyl carbonate, bis(fluoromethyl) carbonate, difluoromethyl methyl carbonate, ethyl(fluoromethyl) carbonate, difluoromethyl ethyl carbonate, 2-fluoroethyl methyl carbonate, 2-fluoroethyl(fluoromethyl) carbonate, 2,2-difluoroethyl methyl carbonate, 2,2-difluoroethyl ethyl carbonate, 2,2,2-trifluoroethyl ethyl carbonate, (2-fluoroethyl) ethyl carbonate, bis(2-fluoroethyl) carbonate, 2,2-difluoroethyl(2-fluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, bis(2,2,2-trifluoroethyl) carbonate, methyl propyl carbonate or ethyl propyl carbonate; The carboxylic acid ester includes at least one of methyl formate, ethyl formate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, 2,2-difluoroethyl acetate or ethyl 2,2-difluoroethyl acetate.

20. The electrolyte according to claim 16, wherein The electrolyte satisfies at least one of the following (e) to (g): (e) Based on the mass of the electrolyte, the mass percentage of the cyclic carbonate W H 0.01% to 30%; (f) the mass ratio of the cyclic carbonate to the linear carbonate is (10-60):40; (g) The mass ratio of the cyclic carbonate to the carboxylic acid ester is (10-60):(20-60).

21. The electrolyte according to claim 1, wherein The electrolyte further includes a second lithium salt, wherein the second lithium salt includes a compound of formula (VA): in, A 51 , A 52 , A 53 and A 54 Each is independently selected from a halogen atom, a group of formula (VB), a group of formula (VC) or a group of formula (VD): represents the binding site with the neighboring atoms; The O in the two binding sites of the group of formula (VC) is connected to B, and k is 0 or 1; R 51 and R 53 Each is independently selected from a substituted or unsubstituted C1 to C6 alkyl group, a substituted or unsubstituted C2 to C6 alkenyl group, and when substituted, each substituent is independently selected from a halogen atom; R 52 The group is selected from substituted or unsubstituted C1 to C6 alkylene groups and substituted or unsubstituted C2 to C6 alkenyl groups. When substituted, each substituent is independently selected from halogen atoms.

22. The electrolyte according to claim 21, wherein A 51 , A 52 , A 53 and A 54 The two adjacent groups form a closed ring structure.

23. The electrolyte according to claim 21 or 22, wherein The compound of formula (VA) includes at least one of lithium tetrafluoroborate, lithium bis(oxalatoborate) or lithium difluorooxalatoborate.

24. The electrolyte according to claim 21 or 22, wherein Based on the mass of the electrolyte, the mass percentage of the second lithium salt is W L2 It is 0.1% to 2%.

25. An electrochemical device comprising the electrolyte according to any one of claims 1 to 24.

26. An electronic device comprising the electrochemical device according to claim 25.

Citation Information

Patent Citations

  • Nonaqueous electrolytic solution and lithium secondary battery using the same

    JP2003208920A

  • Nonaqueous electrolyte and nonaqueous electrolyte secondary battery including the same

    JP2012104439A